Determination of alcohol content in sushi and sushi dipping sauces using headspace GCMS with full evaporation technique approach / Dzulkifly Mat Hashim, Prof. Madya Dr. Faridah Abas and Noorashikin Talip - Mat Hashim, Dzulkifly; Abas, Faridah; Talip, Noorashikin (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
A headspace method coupled with Gas Chromatography Mass Spectrometry (GC-MS) using Full Evaporation Technique (FET) approach was applied to determine ethanol content in sushi and sushi dipping sauces. FET was selected due to its advantages in elimination of matrix effect. Sample size, equilibration temperature and equilibration time were optimized. Optimum conditions of FET were 5 minutes equilibration time at 85°C with sample size less than 50p. No matrix effects were detected on ethanol as well as internal standard in starch solution up to 15% and salt content up to 5%. Thus, a universal calibration curve can be applied for different types of sample; liquid (dipping sauce) and semi solid sample (sushi). Samples with high level of ethanol were quantified using calibration curve at 0.1% to 1.0 % with split ratio of 1:90 whereas calibration curve at 0.0005% - 0.1% with split ratio 1:10 were applied for samples with low ethanol content.